Attention and working memory: two basic mechanisms for constructing temporal experiences - Marchetti, Giorgio (Frontiers in Psychology, 2014)
Various kinds of observations show that the ability of human beings to both consciously relive past events – episodic memory – and conceive future events, entails an active process of construction. This construction process also underpins many other important aspects of conscious human life, such as perceptions, language and conscious thinking. This article provides an explanation of what makes the constructive process possible and how it works. The process mainly relies on attentional activity, which has a discrete and periodic nature, and working memory, which allows for the combination of discrete attentional operations. An explanation is also provided of how past and future events are constructed.